NUTRITIONAL COMPOSITION OF RED SEAWEED Rodhymenia howeana FROM ANCON BAY, PERU - RojasVega, Naddia Carolina (2018)
The objective of this study was to evaluate the nutritional composition of the red alga Rodhymenia howeana. Tests performed: proximal analysis determined according to AOAC, mineral content by atomic absorption spectroscopy, amino acid count by cation exchange chromatography using an amino acid analyzer, vitamin C content and total phenols by spectrophotometry. The most important results of the proximal analysis were 28.56% of protein; 21.08% ash and traces of ethereal extract (lipids) in dry sample. Of the mineral content: iron 502 mg / kg and zinc 18.54 mg / kg of dry sample of algae. The most abundant essential amino acids (mg / 100 g of dry sample) were: valine 95, leucine 116 and lysine 116.2 and among the non-essential ones relevant: alanine 139, aspartic acid 244 and glutamic acid 313. Of the antioxidant components the content of vitamin C was 1.12 mg in 100 g of dry sample and of total phenols was 980.2 mg EAG / 100 g of dry sample. Conclusions: the red seaweed Rodhymenia howeana is a nutritious food and contains antioxidant compounds.